2019
DOI: 10.3390/ijms20246281
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Bisphenol A Atherogenicity Involves Apolipoprotein A-I Downregulation through NF-κB Activation

Abstract: Apolipoprotein A-I (apoA-I) is the major protein component of high-density lipoproteins (HDL), mediating many of its atheroprotective properties. Increasing data reveal the pro-atherogenic effects of bisphenol A (BPA), one of the most prevalent environmental chemicals. In this study, we investigated the mechanisms by which BPA exerts pro-atherogenic effects. For this, LDLR −/− mice were fed with a high-fat diet and treated with 50 µg BPA/kg body weight by gavage. After two months of treatment, the area of athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…We observed that all four SCFAs studied here have anti-inflammatory effects as shown by a lower NF-κB transactivation, which in turn (except for C6) rescued the inflammation-induced reduced hepatic ApoA-I mRNA expression. This seems to be a logical response since the ApoA-I gene contains several NF-κB binding sites in the promoter region in hepatocytes [ 20 , 21 ]. The anti-inflammatory effects of C3, C4 and C5 were confirmed by a reduction in IL-8 secretion into the supernatant of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that all four SCFAs studied here have anti-inflammatory effects as shown by a lower NF-κB transactivation, which in turn (except for C6) rescued the inflammation-induced reduced hepatic ApoA-I mRNA expression. This seems to be a logical response since the ApoA-I gene contains several NF-κB binding sites in the promoter region in hepatocytes [ 20 , 21 ]. The anti-inflammatory effects of C3, C4 and C5 were confirmed by a reduction in IL-8 secretion into the supernatant of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Altered angiogenic activity of the human endometrial endothelial cell was observed following in vitro BPA treatment. Aortic atherosclerotic lesions have been demonstrated as a result of BPA exposure ( Fang et al., 2014 ; Sui et al., 2014 ; Trusca et al., 2019 ) and associated NF-κB activation ( Trusca et al., 2019 ). Basic fibroblast growth factor, a key angiogenic factor, was found to be a poor prognostic factor in NHL ( Pazgal et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bisphenol A (BPA), commonly used in plastic products, has been found in 95% of indoor dust samples [ 45 , 46 ]. Although its inhalation is less than ingestion, BPA may interfere with lipid metabolism and inflammatory responses to increase the risk of atherosclerosis [ 46 , 47 ].…”
Section: Particulate Matter (Pm)—an Intrauterine Toxinmentioning
confidence: 99%